PERSONALIZED MEDICINE: AN INNOVATION IN HEALTH-CARE SYSTEM - KHAMKAT, PIYALI; BARIK, VIVEK; BARIK, BHAKTI BHUSAN; MOHAPATRA, SNEHAMOYEE; KAR, RAJAT (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Personalized medication (PM) is a wide and progressed field of medical science with more accuracy of medication to educate every individual’s clinical data. This model categorizes individuals within discrete subject groups with medical accountability, utility, or products being customized to each group based on their expected response. It is an emergent and rapidly developing method of clinical practice which utilizes advanced technologies that give a conclusion concerning to the prognosis, prevention, recognition, and treatment of diseases. The advantages is to improve the usefulness of PM over traditionally approved drugs due to less toxicity and side effect with therapeutic efficacy, which leads to patient stratification, proactive treatment regimens resulting in reduced health-care costs, and ultimately enhanced the quality of life. This review focused to an extensive understanding of personalized medicines as a major therapeutic approach to overpass the health-care problems and highlights the challenges, current strategies, and future prospective.